2019
DOI: 10.1002/macp.201900265
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Ortho‐Fluoroazobenzenes on Liquid Crystalline Phase Stability and 2D (Planar) Actuation Properties of Liquid Crystalline Elastomers

Abstract: In general, LCEs have gained great interest as stimuli-responsive and actuator materials in the last decades. [7-16] They consist of shape anisotropic molecules (mesogens) that are incorporated in a weakly crosslinked polymeric network (an elastomer). Therefore, they show the entropy elasticity of elastomers as well as the anisotropic characteristics of liquid crystals. Mesogens are either incorporated into the polymer backbone (main-chain LCE) or linked to it via flexible spacers (side-chain LCE). [17-20] The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…The influence of a fluoroazobenzene derivative on the phase stability of a liquid crystal elastomer has been studied. [85] Moreover, how the presence of the visible light-driven component affects the in-plane actuation of the liquid crystal elastomer film has also been investigated. It is found that fluoroazobenzenes are less effective in photoswitching the liquid crystal phase.…”
Section: Azobenzene Derivativesmentioning
confidence: 99%
“…The influence of a fluoroazobenzene derivative on the phase stability of a liquid crystal elastomer has been studied. [85] Moreover, how the presence of the visible light-driven component affects the in-plane actuation of the liquid crystal elastomer film has also been investigated. It is found that fluoroazobenzenes are less effective in photoswitching the liquid crystal phase.…”
Section: Azobenzene Derivativesmentioning
confidence: 99%
“…A number of previously reported azobenzene-LCE systems have shown a certain light-induced reduction of Q, which induces changes in shape. [8][9][10][41][42][43][44][45][46] However, no experimental systems have been developed that show the landscape regarding the stress-strain curves through a straining cycle including viscoelasticity, thereby clearly characterizing and differentiating the basic mechanical properties of the nematic and cis-isomerinduced isotropic phases. Only a few studies on glassy or smectic LCEs have reported their modulus changes upon/ after light irradiation, by which the softening or hardening of materials was evaluated within the small strain regime.…”
Section: Introductionmentioning
confidence: 99%
“…[ 38–40 ] In addition, illumination to induce the shape change is often applied. [ 41–44 ] Topics are here to induce bending or to avoid it (homogeneous shrinking) and the use of visible light. [ 41–43,45 ]…”
Section: Liquid Crystalline Polymersmentioning
confidence: 99%
“…[ 41–44 ] Topics are here to induce bending or to avoid it (homogeneous shrinking) and the use of visible light. [ 41–43,45 ]…”
Section: Liquid Crystalline Polymersmentioning
confidence: 99%